2019
DOI: 10.1016/j.aim.2019.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Exponential growth of colored HOMFLY-PT homology

Abstract: We define reduced colored sl N link homologies and use deformation spectral sequences to characterize their dependence on color and rank. We then define reduced colored HOMFLY-PT homologies and prove that they arise as large N limits of sl N homologies. Together, these results allow proofs of many aspects of the physically conjectured structure of the family of type A link homologies. In particular, we verify a conjecture of Gorsky, Gukov and Stošić about the growth of colored HOMFLY-PT homologies. arXiv:1602.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
(149 reference statements)
1
24
0
Order By: Relevance
“…Furthermore, HOMFLY-PT homologies of a large class of knots satisfy the refined exponential growth, which implies the following relation for their colored superpolynomials P S r (a, q = 1, t) = (P (a, q = 1, t)) r , (2.13) see also [35]. Properties of colored differentials, together with the assumption of the exponential growth, enable to determine an explicit form of the colored superpolynomial P S r (a, q, t) for various knots [38,45,48].…”
Section: Knot Homologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, HOMFLY-PT homologies of a large class of knots satisfy the refined exponential growth, which implies the following relation for their colored superpolynomials P S r (a, q = 1, t) = (P (a, q = 1, t)) r , (2.13) see also [35]. Properties of colored differentials, together with the assumption of the exponential growth, enable to determine an explicit form of the colored superpolynomial P S r (a, q, t) for various knots [38,45,48].…”
Section: Knot Homologiesmentioning
confidence: 99%
“…It has been defined rigorously by mathematicians only recently [34], yet only for the unreduced version, and it is still not suitable for explicit computations (there also exist some constructions in the case of antisymmetric representations Λ r , both reduced and unreduced versions, see e.g. [35], which are conjecturally isomorphic to the homologies corresponding to the symmetric representations). Nonetheless, the conjectural Poincaré polynomial of (reduced) colored HOMFLY-PT homology, referred to as the superpolynomial…”
Section: Knot Homologiesmentioning
confidence: 99%
“…A proof of this can be found in the proof of Theorem 2.15 of [Wed16], which considers colored perturbed sl n cohomology of a (1, 1)-tangle (which for us is the diagram D cut open at the basepoint). Specializing to the 1-colored case and working with a general degree n potential ∂w, Theorem 2.15 identifies the cohomology of the λ-eigenspace of the complex C ∂w (D) with the sl m cohomology of D where m is the multiplicity of λ as a root of ∂w.…”
Section: Proofsmentioning
confidence: 99%
“…For example, Hedden–Ni have shown that they enable Khovanov homology to detect unlinks (it was later proven that the module structure is determined by the bigraded vector space structure in the case of the unlink ), see also Wu for a related result for the triply‐graded homology. Module structures are also important for the comparison with Floer‐theoretic link invariants, see for example, Baldwin–Levine–Sarkar , and the construction of reduced , colored Khovanov–Rozansky homologies .…”
Section: Introductionmentioning
confidence: 99%